Pollution level of trace metals (As, Pb, Cr and Cd) in the sediment of Rupsha River, Bangladesh: Assessment of ecological and human health risks - Kubra, Khadijatul; Mondol, Anwar Hossain; Ali, Mir Mohammad; Palash, Md. Amin Ullah; Islam, Md. Saiful; Ahmed, A. S. Shafiuddin; Masuda, Mst Antara; Islam, Abu Reza Md. Towfiqul; Bhuyan, Md. Simul; Rahman, Md. Zillur; Rahman, Md. Mostafizur (Frontiers in Environmental Science, 2022)
The study area was selected in the Rupsha river basin and the sediment samples were collected to determine trace metal concentrations of As, Pb, Cd, and Cr along with biological effects, and potential ecological and human health hazards for adults and children. The concentrations of trace metals were detected from sixty composite sediment samples using an Atomic Absorption Spectrophotometer (AAS) following some sequential analytical procedures. The mean concentrations of trace metals were organized in the descending order of chromium (Cr) (43.2 mg/kg) > lead (Pb) (29.21 mg/kg) > arsenic (As) (5.18 mg/kg) > cadmium (Cd) (1.8 mg/kg). The current study highlighted that metals were attributed to the riverine sediments from natural sources and other anthropogenic sources, particularly from various industries. Based on the effect-range classifications of threshold effect concentration (TEC) and probable effect concentration (PEC), the trace metal concentrations can impact on the sediment-dwelling organisms occasionally especially for Cr, Cd, and Pb. That is, the concentrations had negative biological consequences on aquatic creatures. The assessed potential ecological risk of Cd offers a significant risk to the aquatic ecosystem, whereas As, Cr, and Cd were in low-risk. Most of the sites of the study area were within the range of moderate risk, indicated by the risk index (RI) values. Furthermore, the applied sediment quality indices, geo-accumulation index (Igeo) indicated that sediment was contaminated by Cd whereas contamination factor (CF) denoted that the sediment of the study area was moderately polluted by Pb. However, pollution load index (PLI) revealed that the study area was polluted for cumulative sence especially in winter season. The age-group risk index (HI) was much lower than the threshold limit of 1, showing that the pollution had no non-carcinogenic risk effect. Total carcinogenic risk (TCR) was less than one-tenth of a percentile. For the sake of human and environmental health, proper monitoring of metal element attribution and strict regulation are required to lessen trace metal pollution.